Os underwood e o anti-heroísmo na série house of cards, da netflix - FERNANDES, Suelen Cristina Nino (2024)
This paper proposes to analyze the archetype of the antihero in the protagonist couple of the House of Cards series, and how this structure of characters contributes to the evolution of the narrative. In the first part, I try to differentiate the term antihero from the concepts of hero and villain, based on script theorists, with especial regard to the construction of characters, as well as highlight the purpose of this type in the development of the relationship with the spectator. In the second part, I analyze the incidence of the antihero in the protagonism of the series produced by the United States in the last twenty years, briefly going through the three phases of the serial narrative in North American television, considering the open TV, cable and streaming, using the characters Tony Soprano and Walter White, from The Sopranos (HBO) and Breaking (AMC), respectively, to introduce the object of study of this research, the couple of protagonists in the Netflix series, Frank and Claire Underwood, analyzing the resources utilized by the creators for the development of the dramatic arc.